1988
DOI: 10.1007/bf01958921
|View full text |Cite
|
Sign up to set email alerts
|

Opioids and behavior: genetic aspects

Abstract: Three animal models, based on genetic differences in endogenous opioid peptides and opioid receptors, are described. Obese mice and rats, whose pituitary opioid content is elevated, may be used to investigate eating disorders. Recombinant inbred strains of mice, which differ in brain opioid receptors and analgesic responsiveness, can be used for study of opioid- and nonopioid-mediated mechanisms of pain inhibition. Individual reactivity to opioids can be examined in C57BL/6 and DBA/2 inbred strains of mice. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Although the inbred strains were chosen for study because of their differences in hippocampal a-bungarotoxin binding, there are many other differences between the strains. In particular, OBA mice, the most deviant strain on both the sensory gating measures and a-bungarotoxin binding, exhibit decreased catecholamine turnover (Kempf et al 1974), increased numbers of forebrain cholinergic neurons (Albanese et al 1985), increased acetylcholinesterase activity (Mandel et al 1974), increased response to opiates (Frischknecht et al 1988), and decreased protein kinase activity (Wehner et al 1990). Given the current understanding of the neurobiology of the hippocampus, none of these differences are likely to account for the differences in auditory response observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the inbred strains were chosen for study because of their differences in hippocampal a-bungarotoxin binding, there are many other differences between the strains. In particular, OBA mice, the most deviant strain on both the sensory gating measures and a-bungarotoxin binding, exhibit decreased catecholamine turnover (Kempf et al 1974), increased numbers of forebrain cholinergic neurons (Albanese et al 1985), increased acetylcholinesterase activity (Mandel et al 1974), increased response to opiates (Frischknecht et al 1988), and decreased protein kinase activity (Wehner et al 1990). Given the current understanding of the neurobiology of the hippocampus, none of these differences are likely to account for the differences in auditory response observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in mice have demonstrated that genetic factors significantly influence the ability of opioids to induce behavioral modifications (Eidelberg et al, 1975;Brase et al, 1977;Frishknecht et al, 1988;Shuster, 1989;Belknap and O'Toole, 1991;Crabbe et al, 1994;Mogil et al, 1996) and that mice of various inbred or outbred strains may differ in sensitivity to behavioral effects of morphine Shuster et al, 1975;Brase et al, 1977;Horowitz et al, 1977). In this regard, over the last two decades DBA/2J and C57BL/6J have been the most studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, these mostly represent individual 'one-off' studies with little attempt being made to follow up the genetic basis or even the biochemical significance of such observations. Many of the studies relating to opioids and opioid receptors have been reviewed by Frischknecht et al 37, and it is clear that a large proportion of papers involve a simple comparison of two strains (frequently C57BL/6 and DBA/2) which differ in behaviour, with an attempt to relate this to a biochemical difference. This can often be misleading (see below).…”
Section: Genetic Variation In Neurotoxicitymentioning
confidence: 99%